Thermal analysis of Micro, Nano- and Non-Crystalline Materials Transformation, Crystallization, Kinetics and Thermodynamics - Šesták, Jaroslav.; Šesták, Jaroslav.; Simon, Peter.; Simon, Peter. (Hot Topics in Thermal Analysis and Calorimetry,, 2013)
Thermal Analysis of Micro-, Nano- and Non-Crystalline Materials: Transformation, Crystallization, Kinetics and Thermodynamics complements and adds to volume 8 Glassy, Amorphous and Nano-Crystalline Materials by providing a coherent and authoritative overview of cutting-edge themes in the field of crystalline materials. In particular, the book focuses on reaction thermodynamics and kinetics applied to solid-state chemistry and thermal physics of various states of materials.   In this volume the fundamental and historical aspects of phenomenological kinetics and the equilibrium background of processes are detailed. Crystal defects, non-stoichiometry and nano-crystallinity, reduced glass-transition temperatures and glass-forming coefficients are covered.  The determination of the glass transition by DSC, the role of heat transfer and phase transition in DTA experiments, and the explanation of DTA/DSC methods used for the estimation of crystal nucleation are reviewed. Structural relaxation and viscosity behaviour in glass and associated relaxation kinetics are also examined, together with the influence of preliminary nucleation and coupled phenomenological kinetics nucleation on both the strongly curved surfaces and nano-particles. The book investigates crystallization of glassy and amorphous materials including oxides, chalcogenides and metals, non-parametric and fractal description of kinetics, disorder and dimensionality in nano-crystalline diamond. Moreover, it analyzes thermal analysis of waste glass batches, amorphous inorganic polysialates and bioactivity of hydroxyl groups as well as reaction kinetics and unconventional glass formability of oxide superconductors.   Written by an international array of distinguished academics, Thermal Analysis of Micro-, Nano- and Non-Crystalline Materials: Transformation, Crystallization, Kinetics and Thermodynamics is a valuable resource to advanced undergraduates, postgraduates, and researches working in the fields of applied material thermodynamics, thermal analysis, thermophysical measurements and calorimetry.